Metal-hydrogen systems with an exceptionally large and tunable thermodynamic destabilization. Issue 1 (December 2017) - Ngene, Peter; Longo, Alessandro; Mooij, Lennard; Bras, Wim; Dam, Bernard
Abstract Hydrogen is a key element in the energy transition. Hydrogen–metal systems have been studied for various energy-related applications, e.g., for their use in reversible hydrogen storage, catalysis, hydrogen sensing, and rechargeable batteries. These applications depend strongly on the thermodynamics of the metal–hydrogen system. Therefore, tailoring the thermodynamics of metal–hydrogen interactions is crucial for tuning the properties of metal hydrides. Here we present a case of large metal hydride destabilization by elastic strain. The addition of small amounts of zirconium to yttrium leads to a compression of the yttrium lattice, which is maintained during (de)hydrogenation cycles. As a result, the equilibrium hydrogen pressure of YH2 ↔ YH3 can be rationally and precisely tuned up to five orders of magnitude at room temperature. This allows us to realize a hydrogen sensor which indicates the ambient hydrogen pressure over four orders of magnitude by an eye-visible color change. Tailoring the thermodynamics of metal-hydrogen interactions is crucial for tuning the properties of metal hydrides but remains difficult to control. Here, the authors create an yttrium hydrogen sensor sensitive to pressure changes of up to four orders of magnitude by adding zirconium into the Y lattice.